2019
DOI: 10.1002/ajh.25683
|View full text |Cite
|
Sign up to set email alerts
|

Gain‐of‐function mutations in PIEZO1 directly impair hepatic iron metabolism via the inhibition of the BMP/SMADs pathway

Abstract: Dehydrated hereditary stomatocytosis (DHS), or xerocytosis, is an autosomal dominant hemolytic anemia. Most patients with DHS carry mutations in the PIEZO1 gene encoding a mechanosensitive cation channel. We here demonstrate that patients with DHS have low levels of hepcidin and only a slight increase of ERFE, the erythroid negative regulator of hepcidin. We demonstrated that at the physiological level, PIEZO1 activation induced Ca 2+ influx and suppression of HAMP expression in primary hepatocytes. In two hep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
50
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 43 publications
(53 citation statements)
references
References 56 publications
3
50
0
Order By: Relevance
“…PIEZO1 knockdown reduced Yoda1-induced ERK1/2 and p38 MAPK phosphorylation but did not affect AKT phosphorylation ( Figure 3E). Supporting our results, a previous report revealed that gain-of-function mutations in PIEZO1 increased Ca 2+ concentrations with ERK1/2 activation, indicating that the PIEZO1 channel activates intracellular signaling [51]. These results suggest that PIEZO1 may function as an ion channel and its expression is involved in agonist-dependent ERK1/2 and p38 MAPK activation in OSCC cells.…”
Section: Piezo1 Is Involved In Agonist-induced Erk1/2 and P38 Mapk Acsupporting
confidence: 91%
“…PIEZO1 knockdown reduced Yoda1-induced ERK1/2 and p38 MAPK phosphorylation but did not affect AKT phosphorylation ( Figure 3E). Supporting our results, a previous report revealed that gain-of-function mutations in PIEZO1 increased Ca 2+ concentrations with ERK1/2 activation, indicating that the PIEZO1 channel activates intracellular signaling [51]. These results suggest that PIEZO1 may function as an ion channel and its expression is involved in agonist-dependent ERK1/2 and p38 MAPK activation in OSCC cells.…”
Section: Piezo1 Is Involved In Agonist-induced Erk1/2 and P38 Mapk Acsupporting
confidence: 91%
“…Our recent genotype-phenotype correlation analysis on 29 PIEZO1-patients demonstrated that most of severely affected patients carried mutations in the pore domain, responsible of the ion passage, while patients showing a less severe phenotype carried mutations in the nonpore domain [7]. In accordance to this finding, the patients here described, both proband and father, showed a mild phenotype and the absence of iron overload [20].…”
Section: Case Presentationsupporting
confidence: 85%
“…Splenectomy is thus contraindicated in this condition. In addition, in patients with DHS iron metabolism should be regularly checked for the risk of developing sever hepatic iron overload [20] (Table 2).…”
Section: Case Presentationmentioning
confidence: 99%
“…Further evidence for the interplay between iron and inflammation comes from studies in DHSt, where hepcidin levels were decreased and erythroferrone (ERFE), the negative regulator of hepcidin, slightly increased. In patients with gain-of-function mutations in PIEZO1, inhibition of the bone morphogenetic proteins (BMP)/small mother against decapentaplegic (SMADs) pathway was involved in hepatic iron metabolism impairment (106). In addition, another important factor for iron balance is emojuvelin (HJV), a co-receptor of BMP that is degraded in juvenile hemochromatosis, causing severe hepcidin deficiency and iron overload.…”
Section: The Vicious Circle Of Iron and The Immune System In Chasmentioning
confidence: 99%